2018
DOI: 10.4274/jtgga.2017.0057
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in papillary thyroid cancer survivors

Abstract: Objective:To evaluate “papillary thyroid carcinoma-pregnancy” interaction among cancer survivors.Material and Methods:The clinical records of 8 pregnant women who received treatment for papillary thyroid cancer before their pregnancy were evaluated. Clinical features, pregnancy/perinatal outcomes and high-risk factors were compared with 45 controls who were randomly assigned from the institutional perinatal medicine database.Results:Patients in the cancer group were older than the control group (34.3 vs 29.8 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Several retrospective studies have discussed the effects of a history of thyroid cancer on obstetric outcomes. [7][8][9] However, no studies have investigated the concurrent thyroid function status of this population. In addition, the previous studies reported conflicting results regarding the risks of postpartum hemorrhage, pre-eclampsia, and preterm birth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective studies have discussed the effects of a history of thyroid cancer on obstetric outcomes. [7][8][9] However, no studies have investigated the concurrent thyroid function status of this population. In addition, the previous studies reported conflicting results regarding the risks of postpartum hemorrhage, pre-eclampsia, and preterm birth.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the abnormal thyroid functions of these patients would influence obstetric outcomes remains unclear and needs to be addressed. Several retrospective studies have discussed the effects of a history of thyroid cancer on obstetric outcomes 7–9 . However, no studies have investigated the concurrent thyroid function status of this population.…”
Section: Introductionmentioning
confidence: 99%